ANALISIS KINERJA REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH SERTA POTENSI PENDAPATAN ASLI DAERAH PADA KABUPATEN MINAHASA UTARA - Sasuwuk, Nathania Ch. E.; Sondakh, Jullie J.; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2016)
Realization of Regional Government budget (APBD) is one of measure instrument to seeÂ the implementation from policies and operationalization implementation of financial regional management for optimal actualization public services. Management potential of Local Revenue (PAD) have to do with correct and appropriate in order to support the progress. The purpose of this research are to know and analyze the realization performance of regional government budget and district own source revenue potential at North Minahasa Region. The result of this research show the regional government budget of North Minahasa in terms of revenue considered good by looking from variance analyzes and tax effectiveness, expect from decentralizationÂ degree analyzes is not good enough or low. While for expense, from variance analyzes over all is good by looking at the budget are well controlled and the impact in the North Minahasa Region for having an surplus from the allocated budget, and for compatibility analyzes expenditure are effective because realization of the expense budget not over amount that has been planned. And for the Own Source Revenue Potential for 2016-2020 seen from tax regional income are 42,78% while from regional retribution are 37,36%. Keywords: performance, government, budget, Potential, Local Revenue